Diurnal vertical migration of some cladocerans in relation to the physico-chemical factors in a fish pond - Bhuiyan, AS; Akhter, S; Quddus, MMA (Dhaka University Journal of Biological Sciences, 2011)
Diurnal vertical migration of four genera of cladocerans, namely Diaphanosoma sp., Daphnia sp., Moina sp. and Bosmina sp., during March to December, 2007 showed that the number of Diaphanosoma sp. was 501 units/1 in the surface layers, 172 units/l in the middle layers and 190 units/l in the bottom layers. The yearly number of Daphnia sp. in surface, middle and bottom layerss was 362 units/l, 46 units/l and 189 units/l respectively. In surface, bottom and middle layers, the number of Moina sp. was 159, 71 and 32 units/l, respectively. Bosmina sp. was 78 units/l in surface, 31 units/l in the middle and 33 units/l in the bottom layers. The number of Diaphanosoma sp., Daphnia sp., Moina sp., Bosmina sp., were 455, 149, 259 and 358 units/l, respectively in the morning, 63, 176, 142, 43 units/l at noon and 107, 55, 28, 59 units/l, respectively in the evening. Throughout the study period the cladocerans were always abundant near the surface during morning and evening. Among the factors responsible for the diurnal movement of cadoceran, light played the most important factor. The relationship between the physico-chemical factors and the cladoceran occurrence in the pond was also explored. Key words: Cladocera; Diurnal migration; Physico-chemical parameters; Fish pond DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8975 DUJBS 2011; 20(2): 147-154